FAKTOR FAKTOR YANG MEMPENGARUHI RENTABILITAS PADA BANK KONVESIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ratih Yuda Wardhani, 09.05.52.0011; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2014)
The purpose of this study was to examine the effect of Adequecy Capital Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR) and to Return on Assets (ROA).This study focused on traditional banking companies listed on the Stock Exchange in 2009, 2010 and 2011. In this study, researchers used purposive sampling and obtain a sample of 30 sample companies. Data using multiple regression analysis.The results showed that the Capital Adequacy Ratio (CAR) is not significant positive effect on return on assets (ROA), Non Performing Loan (NPL) significant negative effect on return on assets (ROA) and the Loan to Deposit Ratio (LDR) is not significant positive effect on Return on Assets (ROA) on Conventional Banks listed on the Indonesia Stock Exchange in the period from 2009 to 2011. Through determination coefficient test result of 0.114 means that 11.4 % of independent variables namely the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL) and the Loan to Deposit Ratio (LDR) can explain the dependent variable Return on Assets ( ROA ) and the rest 88.6 %Â is explained by other factors not revealed in this study.Keywords : Adequecy Capital Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR) and Return on Assets (ROA)